2017
DOI: 10.1002/alr.21984
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TIPE2 in alternatively activated macrophages is associated with eosinophilic inflammation and disease severity in chronic rhinosinusitis with nasal polyps

Abstract: The T-helper 2 milieu is able to induce TIPE2 expression in macrophages. TIPE2-positive M2 macrophages potentially contribute to eosinophilic inflammation and disease progression in CRSwNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…In contrast to the finding in eosinophilic nasal polyps, we did not detect CCL24 expression in macrophages in non‐eosinophilic polyps. Our previous studies demonstrated a predominant M2 phenotype of macrophages in eosinophilic nasal polyps and skewed M1 phenotype of macrophages in non‐eosinophilic nasal polyps . In the present study, we found the macrophages in both eosinophilic and non‐eosinophilic polyps exhibited expression of NK1R.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In contrast to the finding in eosinophilic nasal polyps, we did not detect CCL24 expression in macrophages in non‐eosinophilic polyps. Our previous studies demonstrated a predominant M2 phenotype of macrophages in eosinophilic nasal polyps and skewed M1 phenotype of macrophages in non‐eosinophilic nasal polyps . In the present study, we found the macrophages in both eosinophilic and non‐eosinophilic polyps exhibited expression of NK1R.…”
Section: Discussionsupporting
confidence: 70%
“…Macrophages participate in the primary response to pathogens, coordination of the innate and adaptive immune response, and tissue repair and remodeling . Studies from our laboratory and others have demonstrated an increased infiltration of macrophages in nasal polyps . Moreover, another study suggested that the accumulation and activation of macrophages may induce local adaptive immunity by producing chemokines and recruiting naive T cells and immature dendritic cells in CRSwNP .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For immunofluorescence staining, the tissue sections were first stained with specific primary antibodies (see online) overnight at 4°C. After washing, the tissue sections were incubated with Alexa Fluor 568– and/or Alexa Fluor 488–conjugated secondary antibodies (1:100; Invitrogen, Paisley, UK) at room temperature for 2 hours . Total CD68 + macrophages, IRF5 + CD68 + M1 macrophages, CD163 + CD68 + M2 macrophages, CD206 + CD68 + M2 macrophages, and IL‐10 + CD68 + M2 macrophages were studied .…”
Section: Methodsmentioning
confidence: 99%
“…Although macrophages are involved in many diseases, the role of macrophages in the pathogenesis of CRS is poorly understood. Limited studies have demonstrated increased accumulation of M2 macrophages in CRSwNP, particularly the eosinophilic type . M2 macrophages in CRSwNP have been found to have impaired phagocytosis function.…”
mentioning
confidence: 99%